Atividade de neutrofilos e estresse oxidativo em cordeiros infectados experimentalmente com Haemonchus contortus e suplementados com selênio e vitamina E - Camargo, Emmanuel Veiga de (2010)
The present work had as its objective to assess the oxidizing metabolism of neutrophils, the complete blood count (CBC) and the oxidizing profile of experimentally infected lambs with Haemonchus contortus and supplemented with selenium and vitamin E. 20 male lambs were used, of the Corriedale breed, distributed in four experimental groups with 5 animals: G1 larvae infected animals and supplemented with 0.2mg/kg living weight (PV) of selenite via intramuscular (IM); G2 larvae infected animals and supplemented with 0.2mg/kg PV of selenite IM and 2000 UI per animal of vitamin E IM; G3 larvae infected animals and supplemented with 2000 UI per animal of E IM; G4 larvae infected animals. For the CBC and the biochemical analysis blood collection on the day zero (T0) were carried out, 20 (T1), 40 (T2) and 60 (T3) through jugular venipuncture using vacutainer® tubes. The weighing and the egg determination by gram of animal feces occurred in the same experimental times. For the NBT tests heparinized blood samples were collected in the days zero, 30, 60. Smaller leukocyte values were detected in the supplemented group exclusively with selenium (G1) in relation to the control group (G4) in time 4. Concerning the lymphocytes it was observed a decrease in the G1 in relation to the supplemented only with vitamin E (G3) and G4 in time 3 (T3). For both the tests, NBT-NE and NBT-E there was a decrease in the dye reduction capacity at 60 days in relation to the other times in the groups treated with selenium (G1 and G2). The result of the oxidizing profile showed a significant elevation in the GSH-Px enzyme in the supplemented groups with selenium. Still, the correlation of Pearson revealed the existence of a negative correlation between the concentrations of GSH-Px and TBARS and between this enzyme and the OPG values. Increments were also observed for the catalase enzyme in animal which received the selenium supplementation or when this element was associated to the vitamin E. Smaller values of lipid peroxidation (TBARS) were detected in supplemented animals when these were compared to the control group. These results suggest that the reduced reserves of this antioxidant may exacerbate the generation of free radicals with an increase of the lipid peroxidation and the increase of the environment contamination by the eggs of Haemonchus contortus. Facing these results it is possible to conclude that the selenium supplementation provides a larger protection to the cell antioxidant and to the organism as a whole in lambs experimentally infected by Haemonchus contortus.